Objective assessment of intra‐oral suturing for certification of competency. (29th December 2021) - Shah, Neha P.; Lalli, Anand; Palmer, Julia; Jones, Judith
Abstract: Introduction: Suturing is an essential skill for dental surgeons, yet there is limited evidence for objective measures of competence in this field, which can be applied to licensing or certification processes for dental surgeons to ensure patient safety. Methods: In an objective structured clinical examination (OSCE), participants placed two simple interrupted sutures across a lower molar socket in different suturing environments: [A] commercial simulator, [B] suturing sponge mounted in a 3D printed model, [C] suturing sponge and [D] pig's jaw. Simulators [A] and [B] were mounted into phantom heads in dental chairs, and [C] and [D] were placed on bench tops. Performance indicators, overall task success, quality of sutures placed, length of suture remaining and time taken, were analysed against participants' characteristics such as previous suturing experience. Results: Participants ( n = 38) took significantly longer to successfully complete the sutures on models mounted in a phantom head. Time points at which each model differentiated between competent ( n = 11) and novice ( n = 27) participants were as follows: model A (3:26 min), B (2:41), C (2:05) and D (2:06). Model A showed a significant association between task completion and previous suturing experience ( p = .006). Conclusion: Suturing simulators can be used to objectively differentiate between novice and competent dental surgeons. Model A demonstrated construct validity, as it reliably identified competence using time and task completion as objectively measurable parameters. Utilising model A, the candidate of unknown ability could be identified as appropriately skilled at intra‐oral suturing. To ensure patient safety, further research is needed to identify other objective measures of competence in simulation environments.